Peritoneal washing in gynecological neoplasias - Marcos Paulo R. Sanches (Jornal Brasileiro de Patologia e Medicina Laboratorial, 2019)
Introduction and objective: Peritoneal washing cytology is part of pathological staging of adenocarcinomas of the endometrium and ovary. The objective of this study was to verify the prevalence of cytology positive for malignancy in patients diagnosed with adenocarcinoma of the endometrium or ovary, as well as to verify the association between the positive cytology and the variables age of the patient, histological type of the neoplasm and degree of tumor differentiation. Method: A retrospective and prospective cross-sectional study was carried out through the analysis of peritoneal washing cytology reports and the anatomopathological reports of 43 patients diagnosed with ovarian or endometrial adenocarcinoma, provided by the Pathology Center of Curitiba. Results: In relation to endometrial adenocarcinoma, the prevalence of positive cytologies was 7%. Neither the degree of tumor differentiation (p = 1) nor age (p = 0.233) demonstrated association with such positivity. In relation to ovarian adenocarcinoma, the prevalence of positive cytologies was 20%. The degree of tumor differentiation showed a significant positive association with this positivity (p = 0.044). Age did not show association (p = 0.804). It was not possible to verify association with the histological type of neoplasms due to non-applicability of the statistical test. Conclusion: The prevalence of peritoneal lavage cytology positive for malignancy was 7% in endometrial adenocarcinoma and 20% in ovarian adenocarcinoma. Only the degree of tumor differentiation of ovarian adenocarcinomas showed a significant association with peritoneal washing positivity.